2013
DOI: 10.1176/appi.ps.005012012
|View full text |Cite
|
Sign up to set email alerts
|

Measures of Personal Recovery: A Systematic Review

Abstract: OBJECTIVE Mental health systems internationally have adopted a goal of supporting recovery. Measurement of the experience of recovery is, therefore, a priority. The aim of this review was to identify and analyze recovery measures in relation to their fit with recovery and their psychometric adequacy. METHODS A systematic search of six data sources for articles, Web-based material, and conference presentations related to measurement of recovery was conducted by using a defined search strategy. Results were filt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
202
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 199 publications
(207 citation statements)
references
References 30 publications
3
202
1
1
Order By: Relevance
“…developed to measure individual recovery (Shanks et al, 2013) and the recovery-orientation of services (Williams et al, 2012), which should enable more research and evaluation.…”
Section: Ebr Imentioning
confidence: 99%
“…developed to measure individual recovery (Shanks et al, 2013) and the recovery-orientation of services (Williams et al, 2012), which should enable more research and evaluation.…”
Section: Ebr Imentioning
confidence: 99%
“…The RAS was implemented across a number of countries, therefore accomplishing a sound empirical evidence base (Cavelti et al, 2012;Salzer & Brusilovskiy, 2014;Shanks et al, 2013).…”
mentioning
confidence: 99%
“…Stickley and Wright (2011) observed that in their systematic review of the British literature from January 2006 to December 2009 there are very few research papers focusing specifically on the recovery and mental health concept, furthermore, in their systematic review of the literature directly related to mental health and social inclusion, Wright and Stickley (2013), drew similar conclusions. However conducting this current review, we discovered that in more recent years research directly related to recovery has escalated, especially in relation to understanding the concept, attempting to measure this and suggestions for service development (Borg and Davidson, 2008;Leamy et al, 2011Leamy et al, , 2014Kartalova-O'Doherty et al, 2012;Slade, 2012;Williams et al, 2012;Daley et al, 2013;Gilbert et al, 2013;Shanks et al, 2013). One significant contribution to the knowledge-base of the recovery concept is by Leamy et al (2011) who conducted a narrative synthesis of the literature on personal recovery in order to establish a conceptual framework.…”
Section: Knowledge Of Recovery and Social Inclusion For Life-long Leamentioning
confidence: 99%